TEFL Practices. Scenarios for Research and Reflection (2021)
This compilatory book gives account of a series of topics that have become into inquiry endeavors, pedagogical challenges and research questions for a group of elt women. In this sense, the reader will have the opportunity to delve into current challenges concerning Teaching English as a Foreign Language (tefl).